Face and content validity of sheep heads in endoscopic rhinology training. Issue 10 (15th September 2014) - Awad, Zaid; Touska, Philip; Arora, Asit; Ziprin, Paul; Darzi, Ara; Tolley, Neil Samuel
<x xml:space="preserve">Abstract</x> Background The objective of this study was to assess the face and content validity of the sheep head model in endoscopic rhinology training. Methods This study was a prospective evaluation study. Experienced otolaryngologists and trainees were recruited to complete 7 endoscopic rhinology tasks on pre‐prepared sheep heads. All participants completed a validated 20item questionnaire using a 5‐point Likert scale to assess the model across 4 domains: face validity (FV), global content (GC), task‐specific content (TSC), and curriculum applicability (CTR). Results Participants, including 25 experienced otolaryngologists and 45 trainees, completed all tasks. There were no statistically significant differences between the 2 groups' ratings for FV, GC, or CTR (p = 0.50.7, 0.278, and 0.157, respectively). The model achieved median face validity of 4 (interquartile range [IQR]: 4 to 5) with the agreement of experienced surgeons and trainees alike (95% and 90%, respectively). The median global content was 4 (IQR: 4 to 5 and agreement of 88% and 87%. There was some variation in the rating of task‐specific content. A total of 6 tasks achieved validity with the agreement of experienced otolaryngologists. The highest‐rated tasks were "examination under anesthesia" and "foreign body retrieval." Participants agreed on curriculum incorporation, transferability, and recommendation to trainees (median: 5; IQR: 4 to 5 and 95% to 97% agreement). Conclusion The sheep head model achieved face and content validity for endoscopic rhinology training. It is safe, affordable, and can aid early‐years trainees in acquiring a range of basic endoscopic rhinology skills.